Strategi Sistematis Penguatan Program Studi Ekonomi Syariah dalam Pemenuhan Kriteria Akreditasi LAMEMBA - Tajul ‘Ula; Eni Haryani Bahri (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the systematic strategy for the development of the Sharia Economics Study Program towards superior accreditation based on the LAMEMBA Criteria. The research uses a qualitative approach with an analytical-descriptive method to provide a deep understanding of the observed phenomena. Four LAMEMBA assessors were involved as the main informants. The results of the study show that the Sharia Economics Study Program has designed and implemented strategic policies that support internationalization and improvement of academic quality and tridharma. The internationally oriented vision and mission are implemented through accountability and transparency-based governance. The program prioritizes national and international cooperation through co-funding agreements and collaborative programs. The student admissions and academic services system is designed to attract international students, supported by an Outcome-Based Education (OBE)-based curriculum that is relevant to the profile of graduates. Lecturer development programs, modern facilities, and access to international journals also support learning and research activities. Research and community service is managed collaboratively with international partners, resulting in publications in reputable journals. Overall, the strategies implemented have encouraged consistent achievements in education, research, and internationally oriented community service, strengthening the competitiveness of study programs towards superior accreditation.